Proceso De Enseñanza Aprendizaje De Matematicas Y Su Impacto En El Pensamiento Logico Formal En Los Estudiantes Del Bachillerato Tecnico Del Colegio Agropecuario Jose Rodriguez Labandera De Quevedo” - Rivas Muñoz, Janet (2015)
This research starts from the problem of learning of mathematics in the context of the Middle Education, which has been determined to address the dimensions of mathematics learning, the student's attitude, the social climate of the classroom. This establishes, therefore, the critical situation of the learning of mathematics manifested at different levels and modalities of the education system, in this case the Middle Level Agricultural Technical College Attorney Jose Rodriguez Labandera. Learning, as is well known, is closely two main players, the teacher and student; if one fails, fails learning. Although teachers and students play their roles properly, the relationship does not work if the learning is not well targeted to what determines the curriculum system. Likewise, knowledge of adolescent psychology by the teacher facilitates understanding between him and the student. However, although the teaching meets well their specific task, it is necessary that the student completes his. Difficulties in learning math in high school and there are many, have diverse causes and date back many years. However, when these negative factors are sufficiently reduced, the results are excellent, so it's not down the need for programs that this problem is solved. The latter solution is far from what we all understand as a basic educational principle, which is to provide the student with - a minimum- knowledge required to meet the highest persecuted educational purposes as specified in this research work.